The Influence of Gender, Finance, and Social Change: Study of MSME Entrepreneurship Diversification on the Island of Java - Putri, Alvianita Gunawan; Judijanto, Loso (IJBLE Scientific Publications Community Inc., 2024)
This study explores how gender, finance, and social change influence Micro, Small, and Medium-sized Enterprise (MSME) entrepreneurship diversification on Java Island, Indonesia. MSMEs in West Java are crucial for regional economic growth, but gender disparities and financial challenges impact their development. The research aims to understand the relationships between gender, finance, social change, and entrepreneurial diversification. The study surveys over 130 MSMEs, employing Structural Equation Modeling for analysis. Results show significant connections, emphasizing the need for gender-inclusive policies, improved financial access, and consideration of social dynamics for a diverse entrepreneurial landscape.